Base-Dependent Divergent Annulation of 4-Chloro-3-formylcoumarin and Tetrahydroisoquinoline: Application to the Synthesis of Isolamellarins and Hydroxypyrrolones - Vyasamudri, Sameer; Yang, Ding-Yah (Journal of organic chemistry, 2019)
A series of pyrrolo[2,1-a]isoquinoline and coumarin-fused pentacyclic derivatives were synthesized via base-mediated divergent annulation of 4-chloro-3-formylcoumarin and tetrahydroisoquinoline as a key step. This method was then extended to the preparation of isolamellarins A and B (isolamellarin G trimethyl ether). When exposed to UV light, the pyrrolo[2,1-a]isoquinoline- and coumarin-fused pentacycles B were found to undergo aerobic oxidation to give the corresponding hydroxypyrrolones.